Solidarity Economy and Public Health for Sustainable Development and Community Well-Being - Gómez Rodríguez, Dustin Tahisin (Cooperativismo & Desarrollo, 2024)
The fundamental purpose of this research is to explore and propose strategies for the effective integration of the solidarity economy and public health. This effort is directed towards contributing to sustainable development and improving community well-being. The methodology adopted follows a qualitative approach, implementing two distinct methods for data collection. The first method involves the formulation of search equations through bibliometrics, while the second focuses on a documentary review supported by matrices. A fundamental conclusion that emerges from this study is that the exploration of the dialogues between solidarity economy and public health reveals a transformative potential. This potential translates into the concrete possibility of building more equitable, healthy, and sustainable societies. Collaboration between these fields not only represents a convergence between economic prosperity and collective well-being, but also projects an optimistic vision for the future.